DEVELOPMENT OF SUBSYSTEM FOR DEFINING RECOMMENDED GRINDING WHEEL PARAMETERS - RYBAK, Olga (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article is devoted to issues of choosing a grinding wheel for processing various types of materials. Complications which arise when a tool does not meet the requirements of providing needed surface quality are analysed in this research. The problem of grinding surfaces with a heterogeneous structure is particularly highlighted paying special attention to composite coatings based on superhard compounds. Results of processing workpieces with titanium carbide-based coatings using grinding wheels with different hardness are presented. In order to prevent grinding defects generation and spoiling finished products, the special software subsystem is developed. It is designed to resolve the problem of tool selection automatically. This software is an advanced solution of the considered problem which is usually solved with the use of manuals and handbooks about different grinding wheel properties. As a part of the information system necessary databases are formed to enable software correct functioning. These databases contain information about different characteristics of grinding wheels and the surface material being processed such as kinds of abrasive, their hardness, thermal conductivity, mesh sizes, bonding as well as compound of the processed surface and its density, elasticity, crack resistance. Since required surface quality implies obtaining needed roughness, its value is also taken into account along with other properties. An interface of the developed program module is presented together with its operating algorithm. The suggested program is based on information, analysis, modelling, optimization modules and the module of monitoring grinding regime parameters. In the case that there is no data available for some kind of the surface material, a list of its structure categories can be additionally downloaded. This software allows to prevent from damaging workpieces in the process of their grinding. Therefore, the developed program provides recommendations about appropriate characteristics of the grinding wheel depending on the material of the processed surface and the conditions of the grinding operation.